PENGARUH POLA SOSIALISASI NILAI-NILAI AGAMA ISLAM DALAM KELUARGA TERHADAP PERILAKU RELIGIUS ANAK DI KELURAHAN SUKAJADI KECAMATAN SUKAJADI KOTA PEKANBARU - Elfiyanti, Sri; ', Gimin; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine whether there are patterns of socialization influences the religious values of Islam in a religious family against the behavior of children in urban districts Sukajadi Sukajadi pekanbaru city where at this time the rise of children's negative behaviors such as talking dirty to her, speaking disrespectful to parents, fight even stealing. Negative attitudes that made the child can damage the child's personality and disturbing the public. Population and samples in this study were all Moslem community who have children aged 7-13 years who reside in the Village District of Sukajadi Sukajadi totaling 631 households. While sampling techniques using simple random sampling technique ie 63 respondents 63 respondents parents and one child from the parents aged 7-13 years. Data were collected through interview techniques, questionnaires, and literature. In analyzing the data using quantitative deskripstif. Then the data were analyzed using statistical tests with SPSS version 17. Obtained results it can be concluded that the calculated F (5.617) ≥ F table (2.761) with Sig. (0.002) ≤ (0.05). Thus, there is a significant relationship between the variable patterns of socialization religious values of Islam in a religious family and child behavior variables. That is, that whether or not the child's religious behavior is determined or influenced by the application of the socialization patterns of religious values by parents.Keywords: Socialization patterns, Religious Child Behavior